Determinan pendapatan driver Go-Jek di Kota Jambi - Mutiara Mardatillah; Junaidi Junaidi; Etik Umiyati (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2018)
The purpose of this study was to determine the socio-economic conditions of Go-Jek drivers and the effect of working hours, work experience, age, education and number of passengers on the income of Go-Jek drivers in Jambi City. The data used are primary data obtained from questionnaires and direct interviews with a sample of 98. The sampling method used was incidental sampling. The data analysis tool used is descriptive and quantitative analysis with multiple linear analysis. The socio-economic conditions of Go-Jek drivers in Jambi City are known that the average age is 29 years. The average sex is male. The average marital status is not married. The average education is high school / equivalent. The average number of dependents is 2 people. The average job status is the main. The average side business is in the service sector. The average expenditure for operational costs is for fuel costs, pulses and internet costs, vehicle maintenance costs. The average expenditure for food consumption is for rice and non-rice. The average expenditure for non-food consumption is for education costs, health costs, clothing and others. The simultaneous results of multiple linear regression analysis that the income of Go-Jek drivers in Jambi City is influenced by working hours, work experience, age, education and number of passengers . While partially working hours, work experience, age, college education and number of passengers are significant influences on the income of Go-Jek drivers, while high school education has no significant effect.